2008
DOI: 10.1103/physrevb.77.153405
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of radial deformation of single-wall carbon nanotubes induced by intertube van der Waals forces

Abstract: A cylindrical single-wall carbon nanotube ͑SWCNT͒ deforms in a nanotube bundle by van der Waals forces. The deformation is hard to measure, but is required in order to understand the properties of bundles. Here, we show that such deformations can be measured from changes in electron diffraction intensities. We demonstrate this for a bundle of two SWCNTs ͑d = 2.05 and 1.56 nm͒. Deformation model predicted by atomistic simulations is scaled to fit the experiment. We show that the best fit gives flattening values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Any external forces can lead to the deformation of a tube, so diffraction can alter the structure and lead to mis‐assignment of the chiral indices. Elliptical deformation, asymmetric deformation, and torsional twisting have been reported.…”
Section: Practical Examplesmentioning
confidence: 99%
“…Any external forces can lead to the deformation of a tube, so diffraction can alter the structure and lead to mis‐assignment of the chiral indices. Elliptical deformation, asymmetric deformation, and torsional twisting have been reported.…”
Section: Practical Examplesmentioning
confidence: 99%
“…A quantitative explanation to the buckling behavior of the SWCNT array is explained by making use of the intertube van der Waals forces in the array system. This is due to the fact that in a system of CNT array or MWCNT, van der Waals interaction becomes a decisive component [18,29,30] that decides the mode of buckling.…”
Section: Studies On Swcnt Arraymentioning
confidence: 99%
“…The load transfer mechanism in conventional fiber-reinforced composites has been studied by using the pull-out model for many years [Li-Min et al 1992;Seshadri and Saigal 2007]. Some researchers have conducted molecular dynamic (MD) simulations [Frankland and Harik 2003;Kin and Sean 2001] on CNT pull-out models. Though MD simulation is generally accepted to be more accurate, it is however highly time consuming and costly.…”
Section: Khondaker Sakil Ahmed and Ang Kok Kengmentioning
confidence: 99%
“…Many factors affecting the performance of CNT-reinforced composites include [Ailin et al 2010] mechanical properties of nanotubes as well as matrix, purity, interface characteristics such as interfacial bonding, interactions with host and orientation of CNTs in the matrix. Similar to conventional composites, many research studies also suggested that the performance of CNT-reinforced composites depends critically on the interfacial characteristics between CNT and the matrix material [Kin and Sean 2001;Liao and Li 2001;Manoharan et al 2009;Qian 2003;Salehikhojin and Jalili 2008;Wang et al 2008].…”
Section: Introductionmentioning
confidence: 99%